2014
DOI: 10.4236/ojn.2014.412093
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure and Psychometric Properties of the Danish Adaptation of the Instrument Quality in Psychiatric Care-Forensic In-Patient Staff (QPC-FIPS)

Abstract: There is a need for an internationally standardized and psychometrically tested instrument to measure the perceptions of staff members on the quality of forensic inpatient care provided. The aim of the present study was to adapt the Swedish instrument Quality of Psychiatric Care-Forensic In-Patient Staff (QPC-FIPS) to the Danish context and to evaluate its psychometric properties and factor structure in this context. All permanently employed staff members at all 27 forensic inpatient wards in Denmark were invi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
8
12
0
Order By: Relevance
“…A large number of the mental health professionals (82%) perceived the quality of care as high. This finding is in line with other studies using the QPC instrument as an inpatient staff instrument reporting from various mental health service contexts and cultures, for example in Indonesia (Lundqvist et al, 2019) and in Denmark (Lundqvist et al, 2014). Moreover, some specific results related to the mental health professionals' QPC perceptions caught our interest.…”
Section: Health Professionals' Perceptions Of Quality In Psychiatric supporting
confidence: 90%
“…A large number of the mental health professionals (82%) perceived the quality of care as high. This finding is in line with other studies using the QPC instrument as an inpatient staff instrument reporting from various mental health service contexts and cultures, for example in Indonesia (Lundqvist et al, 2019) and in Denmark (Lundqvist et al, 2014). Moreover, some specific results related to the mental health professionals' QPC perceptions caught our interest.…”
Section: Health Professionals' Perceptions Of Quality In Psychiatric supporting
confidence: 90%
“…Before analysis, imputation was performed by replacing missing data points in questionnaires with the mean of that item in questionnaires having less than 30% missing items. Based on previous research on users perception of the quality of health services [16][17][18][19][20][21][22][23][24][25][26][27][28], we used 80% positive ratings (i.e. a score of at least 3 on QPC-DA items) as a cut off value defining satisfactory quality of service.…”
Section: Discussionmentioning
confidence: 99%
“…The QPC-DA is part of a family of instruments built on a definition of psychiatric care from interviews with psychiatric in-patients and outpatients [13]. In addition to day centre service, the QPC family of instruments currently cover a number of psychiatric service contexts such as in-patient [14], outpatient [15,16], forensic inpatient [17][18][19][20][21][22] and housing services [23,24]. The QPC-DA has been psychometrically tested and shows adequate reliability and validity [12], which makes it suitable for assessing the quality of day centre service from the attendees' perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Revealing the structure of such in-hospital care will facilitate the development of intervention programs that support this transition. Previous studies have identified the structure of the following six types of in-hospital psychiatric care: care and management of inpatients who exhibit self-cutting behaviors [ 23 ]; case management practice [ 24 ]; health services to promote mental health [ 25 , 26 ]; psychiatric services in forensic inpatient care [ 27 ]; therapeutic attitudes of professionals working with drug abusers [ 28 ]; and rehabilitative care in longer term mental health facilities [ 29 32 ]. However, the structure of in-hospital care leading to reduction in early readmission is unclear.…”
Section: Introductionmentioning
confidence: 99%